Knowledge and attitude towards TMS: a brief educational intervention. Issue 1 (13th February 2020) - Yonel, Hakan; Abdelghani, Mohamed
Abstract : In December 2015 NICE recognised the use of transcranial magnetic stimulation (TMS) as a viable option in the management of treatment‐resistant depression. Despite this, uptake of the technique has been slow and only a small number of machines are currently in use across the UK. Here the authors describe an educational initiative to increase clinicians' knowledge of TMS.